A Randomized Trial to Evaluate the Effect of Toric Versus Spherical Contact Lenses on Vision and Eyestrain. Issue 1 (January 2019) - Berntsen, David A.; Cox, Stephanie M.; Bickle, Katherine M.; Mathew, Jessica H.; Powell, Daniel R.; Seidman, Scott H.; Little, Borm Kim; Lorenz, Kathrine Osborn; Nichols, Jason J.
Abstract : Objectives: To compare the effect of toric versus spherical soft contact lenses on objective measures of visual performance using visual acuity and electromyography of the orbicularis oculi muscle. Methods: Current soft contact lens wearers with −0.75 to −1.75 D astigmatism in each eye were binocularly fitted with toric (1-Day ACUVUE MOIST for astigmatism) and spherical (1-Day ACUVUE MOIST) contact lenses in random order. After each fitting and at 1-week follow-up, high- and low-contrast visual acuities were measured. Electromyography was used to objectively evaluate eyestrain. Linear mixed models were used to assess differences between toric and spherical contact lenses. Results: The mean age (±SD) of the 60 participants was 27.5±5.0 years, spherical refractive error was −3.68±2.01 D, and cylinder was −1.28±0.36 D. High- and low-contrast visual acuities with toric lenses were better than with spherical lenses at both fitting (toric high-contrast: −0.065±0.078 and low-contrast: 0.133±0.103 vs. spherical high-contrast: 0.001±0.104 and low-contrast: 0.224±0.107) and follow-up (toric high-contrast: −0.083±0.087 and low-contrast: 0.108±0.107 vs. spherical high-contrast: −0.015±0.095 and low-contrast: 0.211±0.104) (all P <0.0001). Electromyography-measured eyestrain was less with toric versus spherical contact lenses at fitting (least-square ratio of toric over spherical=0.72; P =0.0019) but not at follow-up (ratio=0.86; P =0.11). Conclusion: These results suggest that toric contact lenses provided improved objective measures of vision in a low-to-moderate astigmatic population.